2018
DOI: 10.1021/acs.macromol.8b02223
|View full text |Cite
|
Sign up to set email alerts
|

ω-Norbornenyl Macromonomers: In Situ Synthesis by End-Capping of Living Anionic Polymers Using a Norbornenyl-Functionalized α-Phenyl Acrylate and Their Ring-Opening Metathesis Polymerization

Abstract: An operationally simple approach to preparation of ωnorbornenyl macromonomers (MMs) is reported. Reaction of exo-N-(6hydroxyhexyl)-5-norbornene-2,3-dicarboximide or exo-N-(10-hydroxydecyl)-5-norbornene-2,3-dicarboximide with α-phenyl acrylate (α-PhA) led to novel end-capping agents, NBxPhA [x is 6 (n-hexyl) or 10 (ndecyl)]. Living anionic polymerization of styrene and methyl methacrylate followed by capping with NBxPhA yielded the desired MMs, ω-norbornenyl polystyrene (NBxPS) and ω-norbornenyl poly-(methyl me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 63 publications
1
34
0
Order By: Relevance
“…To confirm this behavior, the bottlebrush polymers made at different MM:G3 and after 53 min of polymerization were examined via SEC where the chromatograms (Figure 2c) showed unimodal curves of each bottlebrush polymer. A long tail at low molecular weight was observed in the polymerization of MM:G3 of 100, which may be from intramolecular chain transfer reactions or some termination during ROMP 71,81. As expected for controlled ROMP of PDMAEA‐C6‐Br 14, the M n was linearly related to the initial MM:G3 (Figure 2d).…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…To confirm this behavior, the bottlebrush polymers made at different MM:G3 and after 53 min of polymerization were examined via SEC where the chromatograms (Figure 2c) showed unimodal curves of each bottlebrush polymer. A long tail at low molecular weight was observed in the polymerization of MM:G3 of 100, which may be from intramolecular chain transfer reactions or some termination during ROMP 71,81. As expected for controlled ROMP of PDMAEA‐C6‐Br 14, the M n was linearly related to the initial MM:G3 (Figure 2d).…”
Section: Resultssupporting
confidence: 54%
“…A low loading of AIBN at 52 °C was used to avoid generating a high number of active radical chains, which subsequently suppressed chain end coupling or termination side reactions to generate MMs with one norbornene group (NB) per chain. Also, low percent conversions (35–45%) were targeted to avoid the polymerization of the norbornene groups 69–71 . 1 H‐NMR spectra confirmed that no undesired reactions took place during RAFT polymerization as indicated by good agreement of relative integration ratios of the norbornene olefin peaks and the peaks associated with the RAFT chain transfer agent at the other end of the chain (Figures S2 and S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations